Increasing Employees Performance through the use of Information Technology, Work-Life Balance and Employee Engagement - Ovalia, Ovalia; Sutaryana, Okky; Farid Ma’ruf (Journal of Accounting and Finance Management, 2024)
This study aims to seek determinant factors contribute to the employee performance in Information Systems and Financial Technology Centre. This study employs a quantitative method with surveys as research instrument. The unit of analysis is the employees of the Information Systems and Financial Technology Centre. The sample of this study use a non-probability sampling, with purposive sampling technique. The data is derived from primary data obtained through distributing questionnaires with likert scale measurements and then processed using the SPSS version 26. The analytical tools used are hypothesis test and coefficient of determination. The results of the research partially show that information technology utilization, work-life balance and employee engagement had positive and significant effect on employee performance. Additionally, the information technology utilization, work-life balance and employee engagement simultaneously had significant effect on employee performance